HPLC analysis of monomers eluted from self-adhesive resin cements - Özgür Genç Şen; Evrim Eligüzeloğlu Dalkılıç; Hacer Deniz Arısu; Hüma Ömürlü; Gürcan Eskitaşçıoğlu (Gazi University, 2016)
OBJECTIVE: The aim of this study was to determine the residual monomer leaching from two self-adhesive resin cements polymerized with Light Emitting Diode (LED) or halogen light curing unit. MATERIALS AND METHOD: Clearfil SA (group A, n = 48) and BisCem (group B, n = 48) cements were inserted in plastic moulds. Each group was further divided into two subgroups. Specimens were light cured with LED light curing unit (LCU) in group A1 and group B1 and halogen LCU in group A2 and group B2 for 20 seconds. The following compounds released from the samples stored in distilled water were analyzed: triethylene glycol-dimethacrylate (TEGDMA) and bisphenol A glycidyl methacrylate (Bis-GMA). Analysis of substances was performed with the use of high performance liquid chromatography, after 1 hour and 24 hour incubation periods. Factorial experimental design and independent t-test was used for statistical analyses. RESULTS: Self-adhesive resin cements released more Bis-GMA and TEGDMA when they were polymerized with LED LCUs (p<0.05). Difference between different time periods was not statistically significant (p>0.05). Clearfil SA cement released more Bis-GMA than BisCem (p<0.05). BisCem released more TEGDMA than Clearfil SA (p<0.05). CONCLUSION: The results of this study showed that the quantity of Bis-GMA and TEGDMA leached from self-adhesive resin cements was influenced by the type of LCU and by the type of self-adhesive resin cement.